Implementing Classroom Action Research Findings for Practical Improvement of the Learning Process: An Evaluation of Their Implementation in School Educational Practices - Rahayu Mardikaningsih; Miftahul jannah; Karimatul Qudsiyah; Ilmiyetul Chonimah; Dewi Kholifah (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to examine teachers' experiences in applying classroom action research results for learning improvement, as well as identifying factors that influence these experiences. The method used in this research is a literature study that collects and analyzes various sources of information relevant to the topic of study. The results of the study show that teachers' experience in implementing classroom action research results is a complex journey influenced by various factors, such as understanding research results, the ability to manage change, work environment support, and resource availability. The experience experienced by teachers can be positive or negative, both of which have an important role in determining the success of the learning improvements made. The implication of this research is the need for comprehensive support from schools and educational institutions to help teachers overcome various challenges faced and improve the quality of the process of sustainable application